Association Between Treatments and Short-Term Biochemical Improvements and Clinical Outcomes in Post-Severe Acute Respiratory Syndrome Coronavirus-2 Inflammatory Syndrome. Issue 5 (23rd March 2021) - Davies, Patrick; Lillie, Jon; Prayle, Andrew; Evans, Claire; Griffiths, Benedict; du Pré, Pascale; Johnson, Mae; Krishnan Kanthimathinathan, Hari; Playfor, Stephen; Deep, Akash; Brierley, Joe; Waters, Gareth; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : OBJECTIVES: To 1) analyze the short-term biochemical improvements and clinical outcomes following treatment of children with post-severe acute respiratory syndrome coronavirus-2 inflammatory syndrome (multisystem inflammatory syndrome in children/pediatric inflammatory multisystem syndrome temporally associated with severe acute respiratory syndrome coronavirus-2) admitted to U.K. PICUs and 2) collate current treatment guidance from U.K. PICUs. DESIGN: Multicenter observational study. SETTING: Twenty-one U.K. PICUs. PATIENTS: Children (< 18 yr) admitted to U.K. PICUs between April 1, 2020, and May 10, 2020, fulfilling the U.K. case definition of pediatric inflammatory multisystem syndrome temporally associated with severe acute respiratory syndrome coronavirus-2. INTERVENTIONS: None. MEASUREMENTS AND MAIN RESULTS: Routinely collected, deidentified data were analyzed. Propensity score and linear mixed effects models were used to analyze the effect of steroids, IV immunoglobulin, and biologic agents on changes in C-reactive protein, platelet counts, and lymphocyte counts over the course of PICU stay. Treatment recommendations from U.K. clinical guidelines were analyzed. Over the 6-week study period, 59 of 78 children (76%) received IV immunoglobulin, 57 of 78 (73%) steroids, and 18 of 78 (24%) a biologic agent. We found no evidence of a difference in response in clinical markers of inflammation between patients with multisystem inflammatory syndrome in children/pediatric inflammatory multisystem syndrome temporally associated with severe acute respiratory syndrome coronavirus-2 who were treated with IV immunoglobulin, steroids, or biologics, compared with those who were not. By the end of the study period, most patients had received immunomodulation. The 12 patients who did not receive any immunomodulators had similar decrease in inflammatory markers as those treated. Of the 14 guidelines analyzed, the use of IV immunoglobulin, steroids, and biologics was universally recommended. CONCLUSIONS: We were unable to identify any short-term benefit from any of the treatments, or treatment combinations, administered. Despite a lack of evidence, treatment guidelines for multisystem inflammatory syndrome in children/pediatric inflammatory multisystem syndrome temporally associated with severe acute respiratory syndrome coronavirus-2 have become very similar in advising step-wise treatments. Retaining clinical equipoise regarding treatment will allow clinicians to enroll children in robust clinical trials to determine the optimal treatment for this novel important condition.